PENDIDIKAN ANTI KORUPSI DALAM MEMBENTUK GENERASI MUDA YANG BERINTEGRITAS - Winna Amelia A. Senandi; Tom Alfa S. Reumi (JURNAL PENGABDIAN PAPUA, 2020)
The application of science and technology in the form of counseling  "Anti-Corruption Education in Forming of Integrated Young Generation" is carried out at the BKKBN GenRe (Generasi Remaja) Ambassador Activity of Papua Province and Pentecostal Children's Services (Pelnap) throughout Jayapura City, with the consideration that each represents the age of adolescents and children school age. The purpose of this research and counseling is to know and understand what is corruption and also to know and understand the causes and forms of corruption. The results of this dedication are, the material provided in counseling on"Anti-Corruption Education in Forming of Integrated Young Generation  can be well received by extension participants with indicators of good responses and responses from participants with various weighted questions raised at the time of counseling take place. Finally, it is expected that counseling on anti-corruption education must be routinely carried out especially for adolescents and school-age children in the context of establishing children's integrity and also as a preventive measure in suppressing future corruption rates, and also as a form of business in establishing the nation's personal child who is honest, great and has the character of a wistle blower. Keywords: Corruption, Anti-Corruption, and Integrated